Peran Pemerintah Kelurahan Sei Kera Hilir II Dalam Kepemerintahan yang Baik - Idris Siregar; Nur Meisah; Nita Permatasari; Muhammad Rayyan Kadafi; Mas Yogi; Dirga Arif Wardana; Syahroni Siregar; Muhammad Fahri Harahap (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Government has a very important role in the development of a country or region. To create a safe country, good governance is needed. Good governance is a follow-up or evolution in administering government from good government changes to governance. The purpose of this research is to find out how the role of the Sei Kera Hilir II village government is in good governance. The method used in this research is to use qualitative methods and data collection techniques by means of observation, interviews and documentation. The results of this study indicate that the village government of Sei Kera Hilir has been running well which is marked by implementing a system of transparency in its governance. In addition, the government has fully involved the community, in this case showing that the kelurahan government plays a role in increasing the principle of community participation. In creating equality and good governance, the lurah has authority and delegates it to village community leaders so that it can run evenly and there is mutual control between the community and village government apparatus. Keywords: Role, Government, Kelurahan